Glial cell line‐derived neurotrophic factor alters lipid composition and protein distribution in MPP+‐injured differentiated SH‐SY5Y cells. Issue 12 (30th April 2020) - Mu, Peipei; Liu, Yuting; Jiang, Shimin; Gao, Jin; Sun, Shen; Li, Li; Gao, Dianshuai
Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by progressive loss of dopaminergic neurons in the substantia nigra and striatum. Glial cell line‐derived neurotrophic factor (GDNF) can effectively promote the differentiation and survival of many types of neurons, especially dopaminergic neurons, suggesting it could be a treatment for PD. Lipid rafts are highly dynamic cell membrane domains that contain numerous signal protein receptors, providing an important platform for signal transduction. Compelling evidence indicates that alterations in lipid rafts are associated with PD, and some studies have reported that GDNF can regulate the expression of caveolin‐1, a lipid raft‐marker protein. However, the precise effects of GDNF on lipid rafts remain unknown. We developed a cellular PD model, purified detergent‐resistant membranes (membrane rafts), and performed proteomic and lipid metabolomics analyses to examine changes in lipid rafts after GDNF treatment. The results showed considerable protein and lipid alterations in response to GDNF, especially altered levels of dopamine‐β‐hydroxylase, heat shock 70 kDa protein, neural cell adhesion molecule, cytoskeletal proteins, and long‐chain polysaturated/unsaturated fatty acids. These findings reveal a new avenue to explore the relationships between GDNF, lipid rafts, and PD and support the hypothesis that GDNF may be a useful treatment for PD. Abstract : In this study, we explored the effect of glial cell line‐derived neurotrophic factor (GDNF) on 1‐methyl‐4‐phenylpyridinium‐injured differentiated SH‐SY5Y cells. The results showed considerable protein and lipid alterations in response to GDNF, especially altered levels of dopamine‐β‐hydroxylase, heat shock 70 kDa protein, neural cell adhesion molecule, cytoskeletal proteins, and long‐chain polysaturated/unsaturated fatty acids. We hope these findings could reveal a new avenue to explore the relationships between GDNF, lipid rafts, and Parkinson's disease (PD) and support the hypothesis that GDNF may be a useful treatment for PD.